A Cauchy-type generalization of Flett's theorem - Markov Lubomir (Demonstratio Mathematica, 2021)
We prove a Cauchy-type generalization of Flett’s theorem and note its geometric interpretations. Several other mean value theorems extending further the result, which involve both real and complex functions, are also proved.